Pengembangan Kualitas Sumber Daya Manusia Sebagai Sumber Belajar Pada Tingkat Dasar Hingga Perguruan Tinggi - Ayun Mira Aprilina; Dewi Agustina; Habibatul Wahidiyah (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
The aim of this research is to explore the role of humans as a source of knowledge in the learning process, as well as how it is developed at various levels of education. The research method used is literature analysis with a qualitative approach. The data analyzed is secondary, coming from existing sources. The research results show that humans, in this context, act as seekers, stores, processors and presenters of information that helps in the learning process and achieves the desired learning goals. In the world of education, the role of teachers as learning facilitators is very important. The level of education must be adjusted to human development as a source of knowledge. Teachers at primary education level, for example, must create a learning environment that is safe, comfortable and arouses students' interest in learning. At the secondary level, creative and interactive learning approaches are necessary. Meanwhile, at the top level, the use of technology and digital resources is key. Apart from teachers, various figures such as speakers, discussion forums, and online learning resources also play a role in individual development as sources of knowledge.